Monetary targeting in practice: The German experience - Peter Schmid (Goethe University Frankfurt, Center for Financial Studies (CFS), 1999)
From the mid-seventies on, the central banks of most major industrial countries switched to monetary targeting. The Bundesbank was the first central bank to take this step, making the switch at the end of 1974. This changeover to monetary targeting was due to the difficulties which the Bundesbank - like other central banks - was facing in pursuing its original strategy, and whichcame to a head in the early seventies, when inflation escalated. A second factor was the collapse of the Bretton Woods system of fixed exchange rates, which created the necessary scope for national monetary targeting. Finally, the advance of monetarist ideas fostered the explicit turn towards monetary targets, although the Bundesbank did not implement these in a mechanistic way. Whereas the Bundesbank has adhered to its policy of monetary targeting up to the present, nowadays monetary targeting plays only a minor role worldwide. Many central banks have switched to the strategy of direct inflation targeting. Others favour a more discretionary approach or a policy which is geared to the exchange rate. In the academic debate, monetary targeting is often presented as an outdated approach which has long since lost its basis of stable money demand. These findings give riseto a number of questions: Has monetary targeting actually become outdated? Which role is played by the concrete design of this strategy, and, against this background, how easily can it be transferred to European monetary union? This paper aims to answer these questions, drawing on the particular experience which the Bundesbank has gained of monetary targeting. It seems appropriate to discuss monetary targeting by using a specific example, since this notion is not very precise. This applies, for example, to the money definition used, the way the target is derived, the stringency applied in pursuing the target and the monetary management procedure.
urn:nbn:de:hebis:30-9257
Keywords: 330